Marjaree Mason Center honors Dr. Torgerson - Uribes, Tom::::::::: (2013)
Dr. Colleen Torgerson, a faculty member in Fresno State's Kremen School of Education and Human Development, will be honored Friday, Oct. 18, as one of the Marjaree Mason Center's Top Ten Professional Women for 2013.